Recovering the African through Afroecology: Ancestral Reverence and Spiritual Regeneration in Black Agrarian Communities - Amenumey, Kareal K. (Tufts Archival Research Center, 2021)
In this thesis I examine how and why members of the Black Dirt Farm Collective invoke African ancestry as important to their work as famers, agrarians, seed keepers, and political organizers. These Afroecologists” articulate ancestral reverence as part of their political identity as ‘African beings’ and as a necessary tool for the healing of generational trauma. I emplace Afroecology by discussing the social and spatial contexts from which it emerges. I reveal the tension between the static cultural imaginaries that Afroecologists pull from and the dynamic nature of culture-making. Afroecologists perform and embody particular images and ideas of “Africanness” which I examine through the framework of what Lorena Munoz terms productive nostalgia. Ancestral reverence emerges as both a tool of emotional healing and a tool to refuse systems of oppression. I interrogate claims of known and imagined ancestral connection to reveal the potentials and limits of ancestral reverence in developing Black political consciousness.; Advisor: Dr. Cathy Stanton